Dampak Orientasi Pasar Dan Inovasi Produk Pada Keunggulan Bersaing (Pt Pegadaian Cab Medan Utama) - Sitorus, Jenni Lestari; Romindo M Pasaribu; Pasaman Silaban (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2023)
PT. Pegadaian is a state-owned company engaged in its main business, namely pawning. PT. Pegadaian is the leader in the national financing market with a high market share and market growth. In the investment product financing line in the form of gold savings and the existence of competitors is a new strategy from PT. Pegadaian to be superior to its competitors. The purpose of this study was to identify and analyze market orientation and product innovation on competitive advantage at PT. Pegadaian Cabang Medan Utama. The method of data analysis was carried out using multiple linear regression methods with a total sample of 380 respondents using gold savings customers. The results of this study are that market orientation has a positive and significant effect on competitive advantage. Pegadaian's gold savings product innovation has a positive and significant effect on competitive advantage. Market orientation and innovation of Pegadaian's gold savings products have a positive and significant effect on competitive advantage.